Match performances of soccer referees: the role of sports science - Weston, M. (Movement & Sport Sciences - Science & Motricité, 2015)
Sports science has extensively quantified the physical demands of soccer refereeing over the past 15 years. Early observational studies provided descriptive accounts of referee match activity profiles. More recently, sports science has examined factors influencing match activities, such as age, competition standard and player activities. Soccer referees` match physical performances are inextricably linked to their ability to make the correct judgment; decision-making is therefore a crucial aspect of refereeing. The aim of this brief commentary is to concisely review the role that sports science has played thus far in the understanding of soccer referees` match performances and then provide some recommendations for future scientific work to assist in the preparation for, and assessment of, match performance.